ANALISIS LINGKUNGAN SOSIAL UNTUK MOTIVASI BELAJAR BAHASA INDONESIA BAGI PENUTUR ASING DI UMJ - Gita, Erlinda Nur Rahma; Sarah, Siti (Prosiding Seminar Nasional Bahasa Ibu, 2025)
BIPA teaching can express ideas, feelings, and participate in a society that uses the language and improve the ability to communicate effectively in Indonesian. This is beneficial for foreign students who want to learn and get to know Indonesia. The purpose of this study is to determine the effect of social environment on foreign students' motivation in learning Indonesian at Universitas Muhammadiyah Jakarta through descriptive qualitative method. This research analyzes the social environment factors that influence the motivation to learn Indonesian. Social environment factors include family, education, and community environments, as well as how these factors impact on foreign speakers' desire to learn Indonesian at Universitas Muhammadiyah Jakarta. Data were collected through the method of see-note and interview. This study shows that a good social environment can have a positive influence on foreign students' motivation to learn Indonesian at Universitas Muhammadiyah Jakarta. The better the social environment, the higher the motivation to learn Indonesian. This study found that in an effort to improve the quality of education and welfare of foreign speakers, the social environment which includes (1) the family environment, (2) the educational environment, and (3) the community environment should be prioritized.